Comparative Analysis of Surgical Outcomes in Chronic Otitis Media with Cholesteatoma: A Study of Canal Wall Up and Canal Wall Down Mastoidectomy: Analysis of Surgical Outcomes in Chronic Otitis Media with Cholesteatoma - Dogar, Muhammad Razzaq; Jilani, Muhammad Aqil; Waheed, Abdul; Anwar, Zubair; Bhatti, Muhammad Imran; Mahar, Ghulam Shabir; Khan, Hina (Pakistan Journal of Health Sciences, 2025)
Chronic otitis media with cholesteatoma (COMC) is a serious, potentially life-threatening middle ear condition characterized by keratinizing squamous epithelium growth, chronic inflammation, and progressive bone erosion. Surgical intervention remains the mainstay of treatment, with canal wall up (CWU) and canal wall down (CWD) mastoidectomies being the primary approaches. Objectives: To evaluate the prevalence, clinical presentation, and surgical outcomes of COMC, comparing the efficacy and complications of CWU and CWD mastoidectomy. Methods: A prospective study was conducted across multiple healthcare centers in Karachi. The study included 136 COMC patients, divided by surgical technique (CWU vs. CWD). Demographics, symptoms, audiometry, recurrence, and complications were assessed over six months. Data were analyzed using SPSS. Results: The mean age of patients was 32.6 ± 12.5 years, with a slight male predominance (60%). Otorrhea (80%) and hearing loss (73%) were the most common presenting symptoms. Recurrence was significantly higher in the CWU group (71.4%) compared to none in the CWD group (p=0.003). However, CWU surgery yielded better hearing outcomes postoperatively (mean gain: 15 dB) compared to CWD (mean gain: 8.9 dB), with a significant difference in final hearing thresholds (p=0.04). Complications were more frequent in the CWD group but were not statistically significant (p=0.19). Conclusions: It was concluded that canal wall down (CWD) offers better disease control with low recurrence, while canal wall up (CWU) preserves hearing. Surgical choice should balance disease clearance and function, with regular follow-up.